New Venture and Family Business Teams: Understanding Team Formation, Composition, Behaviors, and Performance. (January 2013) - Schjoedt, Leon; Monsen, Erik; Pearson, Allison; Barnett, Tim; Chrisman, James J.
New ventures are frequently started by entrepreneurial teams rather than lone entrepreneurs. Often, team members have family ties. Yet, there has been relatively little research on new venture and family business teams. The papers in this special issue address this gap by studying team formation and composition, faultlines among team members, generational involvement in teams, the influence of shared organizational experience and functional homogeneity, and the likelihood of couples, biologically related, and unrelated teams achieving first sales. Combined, they suggest that relationships are more important than skill diversity in determining the effectiveness of both family business and new venture teams.